Theoretical proposals for the managers’ formation management concept - Tamayo Pupo, Arismendis; Serrano Tamayo, Marcos Alexis; Matos Mendoza, David Dainier; Vázquez Betancourt, Pedro (Transformación, 2024)
Objective: This article aims at reviewing the positions of a theoretical conception on the management of the training of executives, focusing on generating greater collective capacity to lead the processes of innovation and organizational improvement.Methods: Given the qualitative nature of this research, a documentary study is chosen in order to examine previous contributions in depth with the help of analysis-synthesis and induction-deduction processes.Results: The object of the theoretical conception is the management of managers’ education aiming at relating the background and renewed approaches that are synthesized in a theoretical, methodological and practical reconstruction that re-signifies it on the basis a new vision of this special object of science, from a theoretical-explanatory and predictive-praxiological perspective. The main theoretical references on which it is based are related to: philosophical foundations (ontological, gnoseological, epistemological, logical and methodological holistic approach); transdisciplinary studies within the paradigm of complexity (hermeneutics); administration as science; education sciences with emphasis on the categories of training and learning and psychological and pedagogical foundations, supported by an andragogic, constructivist and historical-cultural approach to knowledge.Conclusions: The positions that are submitted to the evaluation of the scientific community, enrich and facilitate a theoretical reconstruction of the management process of the training of executives, renewed in correspondence with current changes in Cuban context.
Keywords: Principal; educational management; socialization; personnel administration